Partial Limb Amputation and Successful Prosthetic Adaptation in a Thoroughbred Mare - Serighelli Júnior, Gilberto; Veloso Silva, Caio; Kulik, Karine; Augusto dos Santos Flores, Lucas; Stephany Bezerra Alves, Lorena; Evelyn da Silva, Larissa; Carlos Duque Moreno, Juan; Triches Dornbusch, Peterson (Acta Scientiae Veterinariae, 2025)
Background: Traditionally, severe limb injuries in horses often result in euthanasia. However, advancements in veterinary medicine allow for the treatment and rehabilitation of many of these injuries. Partial limb amputation, combined with the use of prosthetics, can offer a viable alternative to euthanasia, providing the animal with a good quality of life. Studies indicate that mares and stallions have continued to reproduce after partial limb amputation. This approach, however, requires intensive postoperative care and significant lifelong investment. This case report aims to describe a case of a mare that underwent amputation and prosthetic device placement in the left thoracic limb. Case: A 7-year-old Thoroughbred mare, weighing 370 kg, was referred to the Veterinary Hospital (HV) of the Federal University of Paraná (UFPR) in Curitiba, Paraná, Brazil with a 3-year history of complete contracture of the left thoracic limb at the fetlock, along with a wound in the carpal region with granulation tissue. Radiographs revealed subluxation, hyperextension, and bone proliferation of the lateral sesamoid bones and phalanges, along with ligament involvement. After confirming the need for surgery, partial amputation of the left thoracic limb at the metacarpal level was performed, followed by the adaptation of a prosthesis. The amputation involved the sectioning of vessels, nerves, and tendons, while the prosthesis was made of synthetic plaster, aluminum, and vulcanized rubber. During the 1st week of dressing changes, the stump wound was cleaned daily with potassium permanganate, and the dressing was changed. The patient adapted well to the prosthesis, moving without assistance after 10 days. After 2 months of the prosthesis placement, the patient was able to lie down and get up without assistance. Discussion: Partial limb amputation and the adaptation of prosthetic devices could save animals that would otherwise be euthanized due to severe limb injuries. There are few reports in the literature on equine amputations, with some reported causes being chronic septic joints, osteomyelitis, and comminuted open fractures. Partial limb amputation and prosthetic adaptation should be discussed with owners, considering the high complication rates and the quality of life for these horses. One of the main issues related to amputation is the failure of stump healing, especially if infection was present before surgery. Another problem is laminitis in the contralateral limb, due to the excessive weight supported by this limb. Patients with prolonged problems before amputation and those who do not adapt well to the prosthesis are more prone to developing rotation of the 3rd phalanx in the opposite limb. The main complications include severe flexor tendinitis in the early postoperative days and, at 6 months, signs of arthritis and exostosis in the metacarpophalangeal joint. Despite the complications, complete healing can occur between 6 months to a year. Removing hair in the lesion area reduces surface contamination during healing, and antimicrobial or antiseptic agents can be used to facilitate the process. Completely replacing a horse’s limb with an equally versatile device is still not possible, but the idea is to approximate the limb’s mechanics. Equine prostheses are made of carbon fiber, fiberglass, stainless steel, and various types of polypropylene. The new generation of prosthetic devices in horses includes a shock absorption mechanism, which helps reduce pressure on the stump. In the present case report, the base made of vulcanized rubber provided this impact absorption. The need for antimicrobial therapy should be justified before starting, as antibiotics may not be necessary for all wounds. In conclusion, despite high complication rates and chronic treatment needs, amputation can be a viable alternative, particularly for distal limb regions, improving the horse’s quality of life. Keywords: horse, partial limb amputation, prosthesis, rehabilitation. Título: Amputação parcial de membro e adaptação protética em uma égua Puro-Sangue Inglês Descritores: equino, amputação parcial de membro, prótese, reabilitação.